Next-generation video coding and streaming - Bing, Benny (John Wiley & Sons, 2015)
"This book describes next-generation video coding and streaming technologies with a comparative assessment of the strengths and weaknesses. Specific emphasis is placed on the H.265/HEVC video coding standard and adaptive bit rate video streaming"--